UNIT 8.3 Protein Blotting: Immunoblotting. Issue 12 (2nd May 2016) - Ni, Duojiao; Xu, Peng; Sabanayagam, Diviya; Gallagher, Sean R.
Abstract : Immunoblotting (also referred to as western blotting) uses antibodies to probe for a specific protein in a sample bound to a membrane. Typically, a protein sample is first size separated via electrophoresis (e.g., SDS PAGE). However, antibodies used for specific protein detection are restricted by the polyacrylamide gel and, to make the separated proteins accessible, the proteins need to be moved out of the gel and bound to a rectangular sheet of PVDF or nitrocellulose membrane. Specialized blotting equipment electrophoretically transfers the negatively charged proteins from the gel onto the membrane. The nitrocellulose or PVDF membrane binds the proteins as they move out of the gel, producing an exact replica, on the membrane surface, of the original protein gel separation. The membrane is then blocked to prevent any nonspecific protein binding and visualized by specific antibodies to detect the presence or absence of a particular protein. Applications of immunoblotting are many, and include antibody characterization, diagnostics, gene expression, and post‐translational modification analysis. © 2016 by John Wiley & Sons, Inc.